2014
DOI: 10.1371/journal.pone.0112725
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gridded Precipitation Data for Driving SWAT Model in Area Upstream of Three Gorges Reservoir

Abstract: Gridded precipitation data are becoming an important source for driving hydrologic models to achieve stable and valid simulation results in different regions. Thus, evaluating different sources of precipitation data is important for improving the applicability of gridded data. In this study, we used three gridded rainfall datasets: 1) National Centers for Environmental Prediction - Climate Forecast System Reanalysis (NCEP-CFSR); 2) Asian Precipitation - Highly-Resolved Observational Data Integration Towards Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 40 publications
2
38
1
3
Order By: Relevance
“…Other studies using CFSR data not in the Ethiopian context (De Almeida Bressiani et al, 2015;Alemayehu et al, 2015) and with large to very large catchments (13 750 to 73 000 km 2 ) concluded that CFSR data yielded good to very good results and the SWAT model responded reasonably to the data set. One CFSR application in China (Yang et al, 2014) with meso-scale watersheds (366 to 1098 km 2 ) concluded that CFSR data were significantly different and that the CFSR data spatial distribution might be the cause for the weak performance.…”
Section: Roth and T Lemann: Comparing Cfsr And Conventional Weathmentioning
confidence: 99%
“…Other studies using CFSR data not in the Ethiopian context (De Almeida Bressiani et al, 2015;Alemayehu et al, 2015) and with large to very large catchments (13 750 to 73 000 km 2 ) concluded that CFSR data yielded good to very good results and the SWAT model responded reasonably to the data set. One CFSR application in China (Yang et al, 2014) with meso-scale watersheds (366 to 1098 km 2 ) concluded that CFSR data were significantly different and that the CFSR data spatial distribution might be the cause for the weak performance.…”
Section: Roth and T Lemann: Comparing Cfsr And Conventional Weathmentioning
confidence: 99%
“…Twenty sensitive parameters were selected according to previous studies [5,47,66,67] and tested in the SWAT-CUP to perform a sensitivity analysis. Fourteen sensitive parameters were selected according to their performances in the sensitivity analysis, and manual calibration and auto-calibration were performed using a Sequential Uncertainty Fitting (SUFI-2) algorithm to achieve acceptable performance [68][69][70][71][72][73].…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…In addition, in basins upstream of the Three Gorges Reservoir in China, Yang et al [8] compared precipitation datasets derived from land-surface models, reanalysis datasets, and climatology models with in situ station data. They discovered that, in a relatively flat basin, gridded precipitation datasets estimated runoff better than the in situ station data within the SWAT model.…”
Section: Introductionmentioning
confidence: 99%